A disproportionality analysis of FDA adverse event reporting system (FAERS) events for filgotinib - Yinli Shi; Shuang Guan; Sicun Wang; Muzhi Li; Yanan Yu; Jun Liu; Weibin Yang; Zhong Wang (PLoS ONE, 2025)
Background Although filgotinib, a selective Janus kinase 1 inhibitor, has been increasingly applied in the treatment of inflammatory diseases, its comprehensive safety profile remains insufficiently characterized. Using data from the FAERS database covering Q1 2014 to Q2 2024, this study attempts to analyze adverse event signals linked to filgotinib and provide guidance for the safe and sensible clinical usage of filgotinib. Methods From Q1 2014 to Q2 2024, information on adverse drug events (ADEs) associated with filgotinib was gathered. The reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) were among the signal detection methods that were employed for analysis following data normalization. Results Filgotinib was shown to be the main suspected medication in ADE reports, exposing 103 preferred terms (PTs) in 17 system organ classes (SOCs). Infections, gastrointestinal disorders, and musculoskeletal and connective tissue disorders were the most commonly reported adverse effects. Additionally, atrial fibrillation, alopecia, elevated serum creatinine, blood creatinine increased, pulmonary embolism, epididymitis, respiratory failure, and osteopenia were identified as potential disproportionate reporting signals for filgotinib, although these were not listed in the official drug label. Notable significant signals included large intestine erosion (ROR 2186.05, 95%CI (ROR) : 1015.94–4703.86, PRR 2176.18, 95%CI (PRR) : 1014.64–4667.42), mesenteric arterial occlusion (ROR 1832.17, 95%CI (ROR) : 897.68–3739.48, PRR 1822.71, 95%CI (PRR) : 896.17–3707.20), repetitive strain injury (ROR 1149.27, 95%CI (ROR) : 363.16–3637.01, PRR 1147.05, 95%CI (PRR) : 363.24–3622.15), oligoarthritis (ROR 755.02, 95%CI (ROR) : 310.74–1834.54, PRR 752.59, 95%CI (PRR) : 310.60–1823.51), and periostitis (ROR 676.03, 95%CI (ROR) : 319.36–1431.06, PRR 672.98, 95%CI (PRR) : 318.97–1419.87). The subgroup analysis identified obvious sex and age-specific trends in filgotinib-related adverse reactions, emphasizing a higher risk of renal disorders in females, a preponderance of gastrointestinal events in males, and age-dependent trends involving mesenteric occlusion, increased serum creatinine, and immunoglobulin reduction. Conclusion While filgotinib demonstrates therapeutic efficacy, it is associated with a range of potential adverse events, underscoring the need for vigilant clinical monitoring. Particular attention should be given to gastrointestinal, cardiovascular, respiratory, and metabolic complications.